Comparative Expression of Matrix Metalloproteinases in Internal Malignancies and Paired Cutaneous Metastatic Lesions. (May 2015) - Kim, Tae Hyung; Jung, Jin Young; Roh, Hyo Jin; Chung, Kee Yang; Roh, Mi Ryung
Abstract : Background: Matrix metalloproteinase (MMP), tissue inhibitor of metalloproteinase (TIMP), and membrane-type 1 matrix metalloproteinase (MT1-MMP) are thought to be involved in the destruction of basement membrane and stromal invasion by cancer cells. Objective: The aim of this study was to identify and compare MMP and TIMP expression in internal malignancies and paired cutaneous metastatic lesions. Materials and Methods: We compared the expression of MMP-2, MMP-9, MT1-MMP, and TIMP-2 in the internal malignancy and paired cutaneous metastatic lesion using immunohistochemical stains. Results: The cutaneous metastatic lesions expressed significantly more MMP-2, MMP-9, and MT1-MMP and significantly less TIMP-2 than did the paired internal malignancies. In breast cancer, cutaneous metastatic lesions expressed significantly more MMP-9 and significantly less TIMP-2 than did the primary breast cancer lesion. In lung cancer, the cutaneous metastatic lesion expressed significantly more MMP-2 and MT1-MMP than did the primary lesion. In stomach cancer, the cutaneous metastatic lesion expressed significantly less TIMP-2 than did the primary lesion. Conclusions: Our study demonstrates that cutaneous metastatic lesions have different MMPs and TIMP-2 expression patterns compared with their paired internal malignancies. Also, MMPs and TIMP-2 expression differs according to the type of primary cancer.